Impact of rapid urbanization on the modern sedimentary environments in a semienclosed embayment: Tong’an Bay, southeast China coast - Wang, Ai Jun; Ye, Xiang; Zheng, Bin Xin; Mohamad Zulkifley, Mohamad Tarmizi; Wang, Liang; Yu, Dong Sheng (Taylor & Francis, 2018)
Tong’an Bay (TAB) is a semienclosed embayment in the north of Xiamen Island. The sea area of TAB was mainly used for aquaculture in enclosed areas before 2003. Since 2003, the districts surrounding TAB have been undergoing a rapid urbanization process, and the scale of land used for urban construction in these districts has been continuously increasing. Under the backdrop of rapid urbanization, the coastline of TAB has largely been transformed into an artificial coastline. Due to the large scale of land reclamation and, dredging activities and the opening of the Gaoqi-Jimei (GJ) Seawall, there have been relatively significant changes in the coastal and submarine geomorphology in central northern, western, and southern TAB and Wuyuan Bay as well as a significant increase in the area where artificial submarine geomorphologies are distributed; the number of surface sediment types in the TAB has increased, and sediments in the sea area surrounding engineering projects have been coarsening; the sediment transport pattern has not significantly changed at the mouth of TAB and in central northern TAB, but the suspended sediment transport direction near the GJ Seawall has changed to a certain extent.